Environmental resource studies as a new scientific direction - Ivanov, Evgeniy S.; Chernaya, Violetta V.; Pazniak, Siarhei S.; Kochurov, Boris I. (Journal of the Belarusian State University. Ecology, 2018)
The article is devoted to the short argumentation of scientific prerequisites for the emergence and development of a new direction in science – environmental resource studies. For the first time the authors give the definition and reveal the essence of the concept of environmental resource studies.